2018
DOI: 10.2106/jbjs.rvw.17.00156
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Basilar Thumb Arthritis

Abstract: * The thumb carpometacarpal joint is one of the most common locations for degenerative osteoarthritis in the hand.* Conservative therapies include hand therapy, nonsteroidal anti-inflammatory drugs, splinting, activity modification, and corticosteroid injections.* Surgical treatment is divided into trapezium-preserving procedures in addition to trapezium-sacrificing procedures. Trapezium-preserving procedures, which should be performed when the scaphotrapeziotrapezoidal joint is free of disease, include joint … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
1
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 94 publications
0
26
1
5
Order By: Relevance
“…For patients with mild osteoarthritic changes (Eaton classification stage 1 or 2), ligamentoplasty, arthroscopic synovectomy, and first metacarpal osteotomy are selected for thumb CMC joint preservation surgery, whereas, for patients with advanced osteoarthritic changes (Eaton classification stage 3 or 4), arthroplasty such as ligament reconstruction and tendon interposition, arthrodesis, and artificial joint replacement is generally selected as the thumb CMC joint non-preservation surgery. Although the clinical outcome is generally good with each type of treatment [ 30 ], Ogawa et al have reported symptomatic improvement with joint preservation surgery even in patients with advanced osteoarthritic changes [ 25 ]. We believe that joint preservation surgery is preferable for younger patients or those who are involved in heavy labor, although a risk of osteoarthritic change progression exists even after a long-term joint preservation surgery.…”
Section: Discussionmentioning
confidence: 99%
“…For patients with mild osteoarthritic changes (Eaton classification stage 1 or 2), ligamentoplasty, arthroscopic synovectomy, and first metacarpal osteotomy are selected for thumb CMC joint preservation surgery, whereas, for patients with advanced osteoarthritic changes (Eaton classification stage 3 or 4), arthroplasty such as ligament reconstruction and tendon interposition, arthrodesis, and artificial joint replacement is generally selected as the thumb CMC joint non-preservation surgery. Although the clinical outcome is generally good with each type of treatment [ 30 ], Ogawa et al have reported symptomatic improvement with joint preservation surgery even in patients with advanced osteoarthritic changes [ 25 ]. We believe that joint preservation surgery is preferable for younger patients or those who are involved in heavy labor, although a risk of osteoarthritic change progression exists even after a long-term joint preservation surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Thumb CMC arthroscopic hemi- or complete trapeziectomy theoretically overcomes some of these issues, preserving the native static stabilizers of the CMC joint, including the capsule, dorsoradial, and volar beak ligaments. 70 71 72 73 74 Although there have been many case series on CMC arthroscopic outcomes, 32 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 there remains a paucity of large or comparative studies. Therefore, this study assessed the overall outcomes of thumb CMC arthroscopic interventions utilized to treat CMC arthritis, as well as compared the need to perform a soft tissue interposition or suspension after hemitrapeziectomy.…”
Section: Discussionmentioning
confidence: 99%
“…A recent critical literature review published by Gottschalk et al 19 investigated current treatment options for basilar thumb arthritis. According to the authors, trapeziectomy, trapeziectomy with distraction arthroplasty, and trapeziectomy with ligament tendon reconstruction interposition (LTRI) are the surgical techniques supported by good evidence (level I studies with consistent findings) for recommending intervention.…”
Section: Discussionmentioning
confidence: 99%